2021
DOI: 10.3390/polym13122021
|View full text |Cite
|
Sign up to set email alerts
|

Self-Initiated Butyl Acrylate Polymerizations in Bulk and in Solution Monitored By In-Line Techniques

Abstract: High-temperature acrylate polymerizations are technically relevant, but yet not fully understood. In particular the mechanism and the kinetics of the thermal self-initiation is a topic of current research. To obtain more detailed information the conversion dependence of the polymerization rate, rbr, is determined via in-line DSC and FT-NIR spectroscopy for reactions in bulk and in solution at temperatures ranging from 80 to 160 °C. Solution polymerizations revealed that dioxane is associated with the highest r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…For this purpose polymerizations were carried out at temperatures up to 80°C to avoid any contributions from the unknown kinetic data at high temperatures, for example, thermal self‐initiation of the monomer or β scission are negligible up to 100°C. [ 24 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose polymerizations were carried out at temperatures up to 80°C to avoid any contributions from the unknown kinetic data at high temperatures, for example, thermal self‐initiation of the monomer or β scission are negligible up to 100°C. [ 24 ]…”
Section: Resultsmentioning
confidence: 99%
“…Previously it was shown that the overall rate of polymerization, r br , depends on the instantaneous monomer concentration in the system rather than on the starting concentration of the monomer. [ 24 ] In addition, the reaction temperature and the choice of solvent have an influence on r br . When polymerizations at different compositions of monomer and solvent at identical temperatures are monitored by in‐line FT–NIR spectroscopy, data as shown in Figure is obtained.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis afforded a stable 2-propionic-3-methylmaleic anhydride methacrylamide monomer characterized by NMR and electrospray ionization mass spectrometry (ESI-MS, Figures S9–S14). The use of conventional (meth)­acrylate-based monomers should be avoided, as they are more sensitive to exothermic conditions and may suffer from autopolymerization . Moreover, during base-catalyzed amidation of the anhydride, the methacrylate may also get aminolyzed, affording an irreversible ligation of the respective amine …”
Section: Resultsmentioning
confidence: 99%
“…In polymer chemistry, the use of flow technology is a burgeoning field with many advantages over traditional batch processes [106][107][108]. There are myriad analysis techniques which have been successfully adapted for continuous analysis of polymer systems including differential scanning calorimetry in conjunction with Fourier-transform infrared spectroscopy [109] and inline mass spectrometry [110][111][112]. Whilst these techniques clearly show promise for polymer synthesis, for biopolymers and processes which are concerned with the environmental impact of polymeric materials, molecular weight is a key parameter to analyse in a continuous fashion.…”
Section: Defining Reaction Monitoring: Inline Online Atline and Offlinementioning
confidence: 99%